The Investigation of Military Suicides in the 1930—1950 s. - D.N. Shkarevsky (Психология и право)
In the current conditions of aggravation of international conflicts, the study of the problems of suicidal behavior of military personnel is becoming more and more relevant. It is necessary to take into account the available historical experience in this matter. To date, there are no comprehensive studies on this topic. The purpose of the article is to identify the characteristic features of the investigation of suicide cases of servicemen in the 1930s - 1950s. The source base of the study was the unpublished documents of central and regional archives. The author relied on the interdisciplinary methodological approach developed in the works of P. Solomon. The article formulates the following conclusions. The Soviet criminal law provided responsibility for bringing to suicide or assisting suicide and attempted suicide. This norm was not a serious deterrent to suicidal behavior. In the 1930s-1950s there was some improvement in the formal indicators of investigations in these cases. Their quality remained at about the same level, which was evaluated low by higher authorities. The main reasons for this were the lack of incentives for military investigators and the lack of a judicial perspective on these cases.